Aquaglyceroporin AQP7's affinity for its substrate glycerol. Have we reached convergence in the computed values of glycerol-aquaglyceroporin affinity?. Issue 5 (24th January 2022) - Falato, Michael; Chan, Ruth; Chen, Liao Y.
Abstract : AQP7 is one of the four human aquaglyceroporins that facilitate glycerol transport across the cell membrane, a biophysical process that is essential in human physiology. Abstract : AQP7 is one of the four human aquaglyceroporins that facilitate glycerol transport across the cell membrane, a biophysical process that is essential in human physiology. Therefore, it is interesting to compute AQP7's affinity for its substrate (glycerol) with reasonable certainty to compare with the experimental data suggesting high affinity in contrast with most computational studies predicting low affinity. In this study aimed at computing the AQP7-glycerol affinity with high confidence, we implemented a direct computation of the affinity from unbiased equilibrium molecular dynamics (MD) simulations of three all-atom systems constituted with 0.16 M, 4.32 M, and 10.23 M atoms, respectively. These three sets of simulations manifested a fundamental physics law that the intrinsic fluctuations of pressure in a system are inversely proportional to the system size (the number of atoms in it). These simulations showed that the computed values of glycerol-AQP7 affinity are dependent upon the system size (the inverse affinity estimations were, respectively, 47.3 mM, 1.6 mM, and 0.92 mM for the three model systems). In this, we obtained a lower bound for the AQP7-glycerol affinity (an upper bound for the dissociation constant). Namely, the AQP7-glycerol affinity is stronger than 1087/M (the dissociation constant is less than 0.92 mM). Additionally, we conducted hyper steered MD (hSMD) simulations to map out the Gibbs free-energy profile. From the free-energy profile, we produced an independent computation of the AQP7-glycerol dissociation constant being approximately 0.18 mM.